2021
DOI: 10.31234/osf.io/v2rdp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using Eye-Tracking Measures to Predict Reading Comprehension

Abstract: Research on reading comprehension assessments suggests that they measure overlapping but not identical cognitive skills. In this paper, we examined the potential of eye-tracking as a tool for assessing reading comprehension. We administered three widely-used reading comprehension tests with varying task demands to 79 typical adult readers while monitoring their eye movements. In the York Assessment for Reading Comprehension (YARC), participants were given passages of text to read silently, followed by comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 84 publications
(119 reference statements)
0
16
0
Order By: Relevance
“…However, unlike other eye-movement measures, scanpath regularity assesses eye movements relative to the most common reading strategy employed to meet task demands -regardless of what those demands are. Thus, scanpath regularity may prove less susceptible to task-demand effects that influenced word-based measures in previous studies (e.g., Mézière et al, 2022), and hence may provide a more reliable predictor of reading comprehension per se, both as individual predictors and in combination with other eye-movement measures.…”
Section: Scanpaths As a Measure Of Eye-movement Behaviormentioning
confidence: 89%
See 4 more Smart Citations
“…However, unlike other eye-movement measures, scanpath regularity assesses eye movements relative to the most common reading strategy employed to meet task demands -regardless of what those demands are. Thus, scanpath regularity may prove less susceptible to task-demand effects that influenced word-based measures in previous studies (e.g., Mézière et al, 2022), and hence may provide a more reliable predictor of reading comprehension per se, both as individual predictors and in combination with other eye-movement measures.…”
Section: Scanpaths As a Measure Of Eye-movement Behaviormentioning
confidence: 89%
“…The data used in this study was initially collected for a study reported by Mézière et al (2022), which analyzed local and global eye-movements measures, but not scanpath regularity. For convenience we repeat the key points below.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations